The Ergonomic Intervention for Musculoskeletal Diseases and Pain among Oral Health Therapist - Sunarjo, Lanny; Fatmasari, Diyah; Rahmadhani, Febby (Jurnal Kesehatan Gigi, 2024)
Musculoskeletal diseases and pain (MSDs) is commonly occurred among oral health therapist due to improper working positions. This condition can lead to work-related accidents, lower job satisfaction, and increased healthcare costs. In order to address this issue, ergonomic interventions encompassing cognitive, physical, and organizational aspects have been recommended to prevent the occurrence of MSDs. This study aims to assess the effectiveness of ergonomic interventions, specifically using the "EI" model, in alleviating MSDs among oral health therapists. The quality assessment related to pain utilized a validated standardized instrument. A purposive sample of 64 oral health therapists, working as dental assistants in Semarang, Indonesia, participated in the study. Data were gathered through a structured questionnaire incorporating the Nordic Body Map to identify the presence of pain. Additionally, a physiotherapist conducted an objective examination, assessing pain levels using the Visual Analog Scale (VAS). The results of the pain complaints test, as indicated by the Nordic Body Map, revealed a significant p-value of < 0.001, with ∆ mean = 2.19 for the intervention group and 0.91 for the control group. Similarly, the pain level test using the Visual Analog Scale demonstrated a p-value < 0.001, with ∆ mean = 30.38 for the intervention group and 14.91 for the control group. This suggests that the ergonomic model "EI" was significantly effective in reducing complaints of MSDs among oral health therapists.